[14. 4. 12 Kneipab Schewenschleuse mit Pulvermagazin ...] [Aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia wały obronne i śluzę na opływie Motławy na Rudnie, 14. 04. 1912 r.